How Revolutionary is the Holy Spirit? - Webb, Stephen H. (Reviews in religion and theology, 2014)
Most theologians agree that the early church neglected the Holy Spirit in formulations of the Trinity, and in recent years, many books have been written to redress this deficiency. Pentecostal theologians are especially invested in recovering a fuller doctrine of the Holy Spirit. These two monographs, one by an established scholar (Steve Studebaker) and the other by a relative newcomer (Andrew Gabriel), are among the best on this topic. Both are unafraid to be critical of Pentecostal theology and both are valuable for their specificity. Gabriel revises the divine attributes of classical theism while Studebaker goes even further by arguing that the Holy Spirit constitutes the Trinity. Neither author is sympathetic to Social Trinitarianism, and Studebaker in particular is critical of Richard of Saint Victor, who is often credited as an early progenitor of the social model. This first complete translation of Richard's treatise on the Trinity, by Ruben Angelici, reveals a radical view of the Holy Spirit and thus needs to be taken seriously by all future discussions of this topic. Richard not only gives the Holy Spirit its own personal identity but also ties the Spirit to God's power of listening, just as the Son is God's Word.